2022
DOI: 10.1073/pnas.2121465119
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into galanin receptor signaling

Abstract: Significance Galanin exerts various physiological functions through galanin receptors, including antinociceptive activity, depression, and sleep. Here, we reveal a distinct binding mode of galanin peptide in galanin receptors from that of the published structures of peptide-bound GPCRs. Moreover, our work shows that the neuromodulator zinc ion negatively modulates galanin signaling in the central nervous system and further advances our understanding of mechanisms of G protein selectivity of GPCRs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…7 ). Of note, galanin, located far away from the receptor core 60 , 61 , adopted an α-helical structure that sat flat on the top of the orthosteric pocket with formation of massive contacts with ECLs 1-3 and moderate interface area (~1600 Å 2 ). Different from the above peptide-binding modes, INSL5 penetrates into the orthosteric pocket via its B chain C terminus by adopting a single α-helix conformation, which is distinct from all reported peptide-bound class A GPCRs but closer to those seen with class B1 structures bound by peptides, such as glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) and glucagon whose N termini insert deeply into the TMD core.…”
Section: Resultsmentioning
confidence: 99%
“…7 ). Of note, galanin, located far away from the receptor core 60 , 61 , adopted an α-helical structure that sat flat on the top of the orthosteric pocket with formation of massive contacts with ECLs 1-3 and moderate interface area (~1600 Å 2 ). Different from the above peptide-binding modes, INSL5 penetrates into the orthosteric pocket via its B chain C terminus by adopting a single α-helix conformation, which is distinct from all reported peptide-bound class A GPCRs but closer to those seen with class B1 structures bound by peptides, such as glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) and glucagon whose N termini insert deeply into the TMD core.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, most receptors including GPR174, GPR21, GPR52, CCK1R, and NK1R that adopt non-canonical G s coupling mode have been reported to promiscuously couple to other G protein subtypes 9 , 39 42 . Our previous studies have shown that a larger hydrophobic residue (L) at 5.65 is dominant in G q - and G i/o -coupled receptors 37 , 48 . Mutation of L214 5.65 in galanin receptor 2 to alanine almost abolished G q recruitment, indicating its critical role for G q coupling 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown that a larger hydrophobic residue (L) at 5.65 is dominant in G q - and G i/o -coupled receptors 37 , 48 . Mutation of L214 5.65 in galanin receptor 2 to alanine almost abolished G q recruitment, indicating its critical role for G q coupling 48 . Despite differences in conformational changes of TM6 and the hook in Gα between canonical and non-canonical G s coupling mode, a common feature of GPCRs and G s coupling is the insertion of a large hydrophobic residue at the position 34.51 of ICL2 into a hydrophobic groove in the Ras domain of Gα (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 ). Of note, galanin, located far away from the receptor core 55,56 , adopted an α-helical structure that sat flat on the top of the orthosteric pocket with formation of massive contacts with ECLs 1-3 and moderate interface area (∼1600 Å 2 ). Different from the above peptide-binding modes, INSL5 penetrates into the orthosteric pocket via its B chain C terminus by adopting a single α-helix conformation, which is distinct from all reported peptide-bound class A GPCRs but closer to those seen with class B1 structures bound by peptides, such as glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) and glucagon whose N termini insert deeply into the TMD core.…”
Section: Resultsmentioning
confidence: 99%